2011
DOI: 10.1021/jm101315k
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Surfactants Derived from Lysine: Effects of Their Structure and Charge Type on Antimicrobial and Hemolytic Activities

Abstract: Three different sets of cationic surfactants from lysine have been synthesized. The first group consists of three monocatenary surfactants with one lysine as the cationic polar head with one cationic charge. The second consists of three monocatenary surfactants with two amino acids as cationic polar head with two positive charges. Finally, four gemini surfactants were synthesized in which the spacer chain and the number and type of cationic charges have been regulated. The micellization process, antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 54 publications
4
118
1
Order By: Relevance
“…The commercial cationic surfactant hexadecyl trimethyl ammonium bromide ( HTAB) was used as the reference compound. These lysine-based surfactants were synthesized in our laboratory as previously described (Colomer et al 2011a;Pérez et al 2009) and made from natural fatty acid and amino acid organic building blocks. The chemical structure of these compounds was checked by nuclear magnetic resonance and their purity, higher than 99%, was confirmed by elemental analysis and high-performance liquid chromatography.…”
Section: Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The commercial cationic surfactant hexadecyl trimethyl ammonium bromide ( HTAB) was used as the reference compound. These lysine-based surfactants were synthesized in our laboratory as previously described (Colomer et al 2011a;Pérez et al 2009) and made from natural fatty acid and amino acid organic building blocks. The chemical structure of these compounds was checked by nuclear magnetic resonance and their purity, higher than 99%, was confirmed by elemental analysis and high-performance liquid chromatography.…”
Section: Surfactantsmentioning
confidence: 99%
“…Here, the enhanced hemolysis with increasing surfactant concentration could also be due to increased ionic interactions between the negatively charged lipid membranes and positively charged amino groups of the surfactant molecule (Seo and Kim 2010). Furthermore, surfactant properties such as alkyl chain length, position of the cationic charge and head group hydrophobicity can significantly affect surfactant interaction with cell membranes (Colomer et al 2011a). Our results here showed that the compounds with the positive charge in the α-amino group (MKM and PKM) had lower disruptive potency at physiological pH and higher membrane lytic activity in the late endosomal pH range.…”
Section: Hemolysis Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was found that cationic lipids, known as cytofectins, are efficient for delivering functional genes (Brigham et al, 1989), the use of cationic amphiphiles for mediating DNA transfection has increased. Development of resistance in microorganisms towards disinfectants or antibiotics (Heinzel, 1988) brings a necessity to supply presently applied antimicrobial agents by new ones, and thus search for new and effective molecules goes on (Semenov et al, 2011, LaDow et al, 2011, Cole et al, 2011, Colomer et al, 2011, Chanawanno et al, 2010. The strong bactericidal activity of QUATs with long alkyl chains have been known from 1915 (Jacobs & Heidelberger, 1915a, 1915b and studied further on a broad range of microorganisms such as bacteria (both G+ and G-) (Merianos, 1991), fungi (Lukáč et al, 2010, Struga et al, 2008, Pernak & Chwala 2003 and certain viruses (Wong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%